2013
DOI: 10.1111/den.12119
|View full text |Cite
|
Sign up to set email alerts
|

Merits of prophylactic sclerotherapy for esophageal varices concomitant unresectable hepatocellular carcinoma: Prospective randomized study

Abstract: This prospective study demonstrated that prophylactic EIS could prolong the survival of the patients with esophageal varices concomitant with unresectable HCC. Prophylactic EIS for patients with unresectable HCC may be, in part, justified according to the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, there have been no reports regarding the risk factors for EV bleeding after hepatectomy in patients with HCC. The current treatment strategy for EV is based on the finding that endoscopic sclerotherapy prevents EV bleeding in patients with PHT [24][25][26]. High-risk varices may bleed as a result of increased portal venous pressure after hepatic resection, associated with Pringle's maneuver or major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been no reports regarding the risk factors for EV bleeding after hepatectomy in patients with HCC. The current treatment strategy for EV is based on the finding that endoscopic sclerotherapy prevents EV bleeding in patients with PHT [24][25][26]. High-risk varices may bleed as a result of increased portal venous pressure after hepatic resection, associated with Pringle's maneuver or major hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Miyoshi et al reported 3‐year bleeding rates of 50 % for the control group and 18 % for the prophylactic sclerotherapy group in patients with unresectable HCC and concomitant EV [23]. Akahoshi et al reported a cumulative bleeding rate of 48.8 % at 6 months in patients with unresectable HCC and EVs that were likely to bleed, who were treated conservatively [24].…”
Section: Discussionmentioning
confidence: 99%
“…MELD score was statistically significantly larger in group III than in group I and II. Recent research, however, have failed to find any link among sexuality as well as EVs (10) . In addition, there was a link among the size of EVs as well as the age of the individual, with larger EVs being linked to older patients and smaller EV being linked to younger cases.…”
Section: Discussionmentioning
confidence: 95%
“…One possible explanation is that liver disease in men is more severe and carries a higher risk of complications and death than in women. However, several recent research have failed to find a correlation between gender and esophageal varices (9) . Additionally, there was a correlation between the size of the esophageal varices and the patient's age, with larger OV being linked to elderly patients and smaller OV to younger persons.…”
Section: Discussionmentioning
confidence: 99%